Socialization Of Religious Tourism Development As An Effort To Preserve Local Spiritual And Cultural Values In Batam City - Dailami; Moh. Thandzir; Rezki Alhamdi; Natal Olotua Sipayung; Syafruddin Rais; Wahyudi Ilham; Haufi Sukmamedian; Syailendra Reza Irwansyah Rezeki; Gita Irmalya (JURNAL KEKER WISATA, 2026)
The Community Service Activity (PKM) with the title "Socialization of Religious Tourism Development as an Effort to Preserve Spiritual Values and Local Culture in Batam City" aims to increase public understanding and awareness of the importance of religious tourism development as part of the preservation of local spiritual and cultural values. This activity is carried out through socialization, counseling, and interactive discussions involving the community, religious leaders, and local stakeholders. The material presented includes the concept of religious tourism, the potential of religious destinations in Batam City, as well as sustainable management strategies based on local wisdom. The results of this activity show an increase in public understanding of the importance of maintaining spiritual and cultural values in tourism development. In addition, this activity also encourages the active participation of the community in developing and promoting religious tourism as a local identity that has economic and social value. Thus, this PKM activity is expected to be the first step in building synergy between the community, government, and academia in supporting the sustainable development of religious tourism in Batam City.